Psychological Aspects of Developing Technical Creative Abilities in Students (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The scientific article is devoted to the development of technical creativity exercises in students using technical abilities in drawing lessons, and it describes in detail the views of psychologists who have studied this area.